Inventory cost framework for managing the petroleum product reorder point and order quantity policies. Issue 1 (1st January 2018) - Nwanya, Stephen C.; Isi, Chibuike K.
Abstract: This work developed the optimal inventory cost framework for managing the reorder-point and order quantity policies of a petroleum products service station experiencing frequent inventory outages. The specific objectives of the study include formulating an optimal cost model for evaluating inventory performance of premium motor spirit, determining the amount of petrol emission due to evaporation and computing the optimal parameters. To realize those objectives, primary data for the study were obtained through a mix of field measurements and analytical methods. For 365 days, the stock on-hand was continuously monitored after each daily transaction by physical measurement, using a calibrated dipping stick. Also, the evaporated PMS was estimated and the equivalent cost incorporated to the holding cost function through the least square method. Based on the differentiation of the sum of holding, ordering and crashing costs functions, with respect to lead time and order quantity decision variables, the inventory cost framework was formulated. The results show that the framework yielded optimal supply at lower inventory cost and a 10% increase of service level above the current level of 80%. So, in managing the fuel stock, the monthly decision rule is to ensure that not less than 195, 119.84 litres order is replenished as stock in inventory drops to 29, 743.54 litres reorder level. Inclusion of least square cost method to account for the evaporated quantity is a novelty to this proposed cost structure. The developed model guarantees reliable information and can be a benchmark for management of other petroleum products.